The Influence of the Use of Cooperative Learning Models, Individual and Learning Motivation in Improving Student Learning Outcomes - ., Sumarwoto (International Journal of Educational Technology and Learning, 2021)
The purpose of this research to determine the effect of learning outcomes between cooperative and individual learning models applied to Class VII students in Civics subjects at SMP Negeri 1 Trenggalek, knowing the difference in learning outcomes between students who have high motivation, high learning and students who have low motivation in Class VII students in Civics subjects at SMP Negeri 1 Trenggalek and know the interaction between cooperative learning models, individual and learning motivation on the learning outcomes of Class VII students in Civics subjects at SMP Negeri 1 Trenggalek. The analysis used using data analysis used in this study is to use two-way analysis of variance techniques. The results of the study explain that there are differences in the learning outcomes of class VII students who are taught using the cooperative method compared to students who are taught using individual learning at SMP Negeri 1 Trenggalek. There are differences in the learning outcomes of class VII students who have high learning motivation compared to class VII students who have low motivation at SMP Negeri 1 Trenggalek. There is an interaction between the application of cooperative learning methods and class students' learning motivation on the learning outcomes of class VII students at SMP Negeri 1 Trenggalek, where classes that apply cooperative learning methods to students who have high motivation have better learning outcomes.